Nubuatan Tentang Mesias dari Kitab Para Nabi - Kuncoro Condro (Sekolah Tinggi Theologia Nazarene Indonesia, 2017)
The concept of the Messiah according to the Old Testament prophets originated because of the threat that made the Kingdom of Israel and Judah fell into the hands of the enemy and made them live in misery. The Prophets delivered the news of the coming of a king from David's descendant who was raising the fallen kingdom of David. This Messiah's person is very powerful because there is a Spirit of God that is in him so as to be able to restore, rule the kingdom so that the atmosphere of peace, full of abundance and security and justice is felt by the people. Messiah is a liberator who is able to release his people from the threat of foreign nation. The concept of the Messiah as a political liberator and power ultimately held by the Israelites to the present day.